Mídias sociais nas bibliotecas da UFRJ: adoção e monitoramento - Anjos, Cláudia Regina dos (2016)
This study investigated the use of social media in thirty-one libraries of the Federal University of Rio de Janeiro to understand how to use these tools and weave guidelines for the proper use of monitoring tools in biblioteconômico scenario. The study was based on observation techniques and interviews to ascertain the perception of librarians and users in the use of media in the context of academic libraries. While the importance of communication channel that is recognized by both respondents as a means of promoting products and services, the results indicated that social media are not the dominant elements of the universe of academic libraries. The study is plus a Basic Guide to Using Social Media, directed to the professionals of the information, which are presented suggestions for use, monitoring and measurement of organizational performance communication in social media.